Quran-Based Inquiry Learning: An Analysis of the Pedagogical Values of QS. Al-An'am 75-79 and QS. Al-Ghasiyah 17-21 for Enhancing Students' Rational Faith - Zidny Hikmatiar; Cucu Surahman; Elan Sumarna; Muhammad Aldam Shaka Pradipta; Hadiana Nasrullah (IAIN Manado, 2026)
Although the Qur'an emphasizes rational contemplation in developing faith (aqidah), modern Islamic education often relies on dogmatic approaches that neglect active cognitive engagement. To address this gap, this study formulates a Qur'an-based inquiry learning model conceptually grounded in QS. Al-An'am (75–79) and QS. Al-Ghasyiyah (17–21). Applying qualitative thematic analysis to representative classical and modern Qur'an exegeses, this research extracts Islamic pedagogical (tarbawy) values through source triangulation. The findings identify four core pedagogical components: (1) positioning the learner as an active cognitive agent, (2) redefining the educator as an inquiry facilitator, (3) contextualizing learning objects within immediate reality, and (4) designing scaffolded reflection processes. These components are epistemologically anchored in the Qur'anic concepts of ro'a (existential awareness) and nazhara (intense empirical observation). Unlike secular Western inquiry models, this synthesized Qur'an-based framework integrates systematic empirical observation with transcendental realization, successfully facilitating a cognitive transition from inherited imitation (taqlid) to conscious belief. These insights offer concrete implications for curriculum design and teacher training, presenting a novel pedagogical framework that harmonizes critical reasoning with spiritual growth in the modern era.